2016
DOI: 10.1152/ajprenal.00340.2016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in chronic kidney disease: a systematic review

Abstract: Insulin resistance (IR) is an early metabolic alteration in chronic kidney disease (CKD) patients, being apparent when the glomerular filtration rate is still within the normal range and becoming almost universal in those who reach the end stage of kidney failure. The skeletal muscle represents the primary site of IR in CKD, and alterations at sites beyond the insulin receptor are recognized as the main defect underlying IR in this condition. Estimates of IR based on fasting insulin concentration are easier an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
230
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(261 citation statements)
references
References 232 publications
3
230
0
6
Order By: Relevance
“…15,16 Insulin resistance manifests from the early stages of renal impairment, and diabetes mellitus co-exists in one third of people with CKD. 15,16 Insulin resistance manifests from the early stages of renal impairment, and diabetes mellitus co-exists in one third of people with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Insulin resistance manifests from the early stages of renal impairment, and diabetes mellitus co-exists in one third of people with CKD. 15,16 Insulin resistance manifests from the early stages of renal impairment, and diabetes mellitus co-exists in one third of people with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…A potential unifying explanation for the observed dyslipidaemic pattern of CKD is that of insulin resistance which has been shown to be an early metabolic alteration in CKD and independent of diabetes and obesity in this population 25. More research is, however, needed to further the understanding of the likely complex relationship between kidney function, insulin resistance and lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…In the measurements of IR and beta cell function, the "gold-standard" method (e.g., hyperinsulinemic-euglycemic clamp and the hyperglycemic clamp test) is known to more accurate than HOMA indices. Some studies suggested that HOMA-IR is imperfect to estimate insulin resistance in CKD due to its several limitations [45,46]. Therefore, in future studies, it is necessary to study the relationship between CKD and IR and beta cell function using the "gold-standard" method.…”
Section: Discussionmentioning
confidence: 99%